ANALISIS PEMASARAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DI KECAMATAN TODANAN KABUPATEN BLORA - Sasongko, Lutfi Aris; Ganestyani, Indah Arum; Muâ€™adzim, Agus (Universitas Wahid Hasyim, 2024)
White oyster mushrooms are an agricultural product that is easily damaged so they must be marketed immediately through marketing activities. Obstacles in marketing efforts are the length and shortness of marketing channels which can affect margins, farmer's share and marketing effectiveness. The research method used is a quantitative descriptive method. The farmer sampling technique uses saturated sampling, while the trader sample uses snowball and incidental techniques. Based on the research results, three marketing channels for white oyster mushrooms were obtained in Todanan District, Blora Regency, namely marketing channel I: farmers â†’ final consumers, channel II: farmers â†’ retailers â†’ final consumers, and channel III: â€œfarmers â†’ wholesalers â†’ retailers â†’ final consumer.â€The margin and farmer's share for each channel formed, namely channel I, is IDR. 0/kg and 100%, channel II Rp. 9,000/kg 64%, and channel III Rp. 10,000/kg and 60%. All marketing channels for white oyster mushrooms in Todanan District, Blora Regency are efficient based on the marketing efficiency criteria, namely â‰¤ 50%.Â Kata kunci: Efficiency, farmerâ€™s share, margin, marketing channels, white oyster mushrooms